2016
DOI: 10.21037/jtd.2016.10.36
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of non-AIDS patients pathologically diagnosed with pulmonary cryptococcosis

Abstract: PC was not rare in immunocompetent host in southern China. Special differences remained in clinical manifestation and radiological findings of PC between immunocompromised and immunocompetent patients. Future work on the mechanisms of possible differences is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 25 publications
9
62
0
Order By: Relevance
“…[ 6 7 8 9 ] In radiography, some studies reported that chest radiological findings of pulmonary cryptococcosis were untypical and varied. [ 6 22 23 ] Many studies found that pulmonary nodules and mass were more common. [ 6 8 24 ] Lindell et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 7 8 9 ] In radiography, some studies reported that chest radiological findings of pulmonary cryptococcosis were untypical and varied. [ 6 22 23 ] Many studies found that pulmonary nodules and mass were more common. [ 6 8 24 ] Lindell et al .…”
Section: Discussionmentioning
confidence: 99%
“…to cause endovascular infection and endocarditis is very low. Interestingly, cryptococcosis occurs more frequently in immunocompetent patients than in immunocompromised patients in China [7][8][9][10] . The mechanism of this is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent symptoms in our patients with pulmonary cryptococcosis included cough and expectoration were also found in our series and in those in previously published reports. [4,[16][17][18][19] Our data on laboratory findings, including WBC, neutrophils, Hb, PLT, and plasma PCT level suggested that there were no significant difference between two groups (Table 1). It may confirm that cryptococcosis could dampen pulmonary neutrophil recruitment and inflammatory cytokine production in immunocompetent hosts, which affects the immunity of a healthy subject.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary cryptococcosis caused by infection with Cryptococcus neoformans C. Cryptococcus complexes is common in patients with immune dysfunction and it has become a emerging disease in patients with good immune function. [1][2][3]Some reports [4,5] revealed that pulmonary cryptococcosis occurs more frequently in immunocompetent patients than in immunocompromised patients.…”
Section: Introductionmentioning
confidence: 99%